Specyfika organizacji społecznej i państwowej Wajnachów w okresie XV-XVIII wieku - Szukalski, Jerzy (Przegląd Wschodnioeuropejski, 2026)
The Vainakhs, who include the Chechens, Ingush and Bacoi, were the only people of the North Caucasus who managed to resist the 13th-century Mongol invasions, taking refuge in hard-to-reach mountain valleys in present-day Chechnya. After the fall of the Golden Horde and Timur’s State in the Caucasus, a new balance of political power emerged, ensuring relative security for the Vainakhs. This allowed for the continuation of the consolidation of the Caucasian highlanders, which had begun in the 14th century, and the emergence of a specific social and state organization at the end of the 15th century. It was based on a federation of clan- -tribal organizations, creating thukums and taipas. The supreme body of this state was the State Council, called Mehk-Kheł, which performed legislative, executive, judicial and control functions. The social organization of the Vainakhs in the period under discussion also showed specific features. Its basis was the freemen and a small number of dependent people recruited from among prisoners of war and freedmen. Despite the increasing stratification of wealth and attempts at subjugation by Kabardian, Kumyk and Avar princes and khans, the vast majority of uzdeni managed to maintain their independence. The Vainakh state organization system remained unchanged until the beginning of the 19th century.